P016 Updated Clinical Practice Guidelines for JIA management adopting Treat to Target approach: the Egyptian College of Paediatric Rheumatology initiative. (11th November 2021) - El Miedany, Y; Hassan, M; Salah, S; Lotfy, H; Abdulhady, H; Salah, H; El Gaafary, M; Abd El-Latif, E; Farag, Y; Eissa, M; Esam Maher, S; Radwan, A; et al.
Abstract: Background: There is an unmet need from paediatric rheumatologists and rheumatologists, managing children with JIA, for a well formulated guidelines aiming at achieving better outcomes of their patients. To establish adequate and easily adopted guidelines in management of different variants of JIA in a relatively low resources country. Method: This study was carried out to achieve an Egyptian expert consensus on a treat-to-target management strategy for Juvenile Idiopathic Arthritis using Delphi technique. The preliminary scientific committee identified a total of 17 key clinical questions according to the Patient/Population, Intervention, Comparison, and Outcomes (PICO) approach. An evidence-based, systematic, literature review was conducted to compile evidence for the benefits and harms associated with JIA treatments. The core leadership team identified researchers and clinicians with expertise in JIA management in Egypt upon which Experts were gathered from different governorates and health centres across Egypt. Delphi process was implemented (2-rounds) to reacha consensus on the management recommendations of Egyptian JIA patients. Results: An online questionnaire were sent to expert panel ( n = 27), of whom 26 participated in the two rounds. At the end of round 2, a total of eighteen (18) recommendation items, categorized into 4 sections to address the main 4 JIA categories, were obtained. Agreement with the recommendations (rank 7–9) ranged from 83.2–100% (average 86.8%). Consensus was reached (i.e. ≥75% of respondents strongly agreed or agreed) on the wording of all the 18 clinical standards identified by the scientific committee. Algorithms for the management of JIA polyarthritis, oligoarthritis and systemic JIA have been suggested. Conclusion: A wide and representative panel of experts established a consensus regarding the management of JIA in Egypt. The developed guidelines provide a comprehensive approach to the management of JIA for ll Egyptian healthcare professionals who are involved in its management for follow up and frequent evaluation of these guidelines.